Monospecific culture isolation of some phytoplanktonic algae of Naples gulf - Mihnea, Pia Elena; Laurenzi, Tullio (Cercetări Marine - Recherches Marines, 2026)
Taking into consideration the ecological and physiological requirements of planktonic and benthonic unicellular algae, a new method was established for isolation in monospecific cultures. For those organisms, that developed well on the solid media, Mulvany’s microbiological method (1969) was adapted.